ACUTE AND SUB-ACUTE DERMAL TOXICITY STUDIES OF MORINDA CITRIFOLIA L. FRUIT EXTRACT IN SPRAGUE DAWLEY RATS - Zahi, Ali Khairullah; Hamzah, Hazilawati; S, Hutheyfa; Shaari, Mohd Rosly Shaari; Sithambaram, Shanmugavelu; Othman, Hemn Hasan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: Morinda citrifolia is one of the most significant plants that are used in traditional medicine. However, details of the dermal toxicity of M. citrifolia are still undiscovered. The objective of this study is to investigate the in vivo acute and subacute dermal toxicity of ethanolic extract of M. citrifolia fruit extract at doses 2000 and 5000 mg/kg in acute and 500, 1000 and 2000 mg/kg body weight in rats. Methods: In acute experiment, a total of 40 female rats were divided into eight groups, each group had five rats, and a total of 66 male rats were divided into 11 groups of six rats in sub-acute experiment. Results: The extract at a single dose of 2000 and 5000 mg/kg of body weight did not produce treatment-related signs of toxicity or mortality in any of the animals tested during the 14-day observation period. In the repeated dose 28-day study, the application of 500, 1000 and 2000 mg/kg of body weight/day of fruit extract revealed no significant change (p>0.05) in bodyweight, hematological and biochemical parameters compared with the control group. Similarly, grosspathology and histopathology examinations of liver, spleen, kidneys, and skin did not reveal any morphological alteration. Conclusion: Overall, the results recommend that the close application of M. citrifolia fruit extract did not deliver any critically dangerous impact in rats. Subsequently, the concentrate can be employed for pharmaceutical plans. Keywords: Morinda citrifolia, Acute dermal toxicity, Fruit extract, Sub-acute dermal toxicity